Race by Sex Differences in Depression Symptoms and Psychosocial Service Use Among Non-Hispanic Black and White Patients With Lung Cancer - Traeger, Lara (American Society of Clinical Oncology, 2014)
PURPOSE: This study examined race by sex differences in depression symptoms and psychosocial service use (pastors, social workers, mental health workers, support groups) among patients with lung cancer. PATIENTS AND METHODS: The multiregional Cancer Care Outcomes Research and Surveillance study surveyed black and white adults with stages I to III lung cancer (n = 1,043) about depression symptoms, interest in help for mood, and psychosocial service use. Multivariable logistic regression was used to evaluate race/sex differences in depression symptoms (modified Center for Epidemiologic Studies Depression Scale ≥ 6) and psychosocial service use, independent of demographic, clinical, psychosocial, and behavioral covariates. RESULTS: A total of 18.2% screened positive for depression symptoms. This proportion was highest among black men (24.7%), followed by white women (20.6%), black women (15.8%), and white men (15.0%). In adjusted analyses, white women showed greater risk for depression symptoms relative to black women (P = .01) and white men (P = .002), with no other differences among groups. Black patients were less likely than white patients to receive desired help for mood from their doctors (P = .02), regardless of sex. Among all patients, black women were most likely to have contact with pastoral care and social work. CONCLUSION: Race and sex interacted to predict risk of depression symptoms. Covariates accounted for elevated risk among black men. White women showed greater risk than black women and white men, independent of covariates. Black patients may experience greater barriers to receiving help for mood from their doctors. Race by sex differences in contact with psychosocial services highlight potential differences in the extent to which services are available, acceptable, and/or sought by patients.